2022
DOI: 10.3390/ijms23158629
|View full text |Cite
|
Sign up to set email alerts
|

Effects of MICU1-Mediated Mitochondrial Calcium Uptake on Energy Metabolism and Quality of Vitrified-Thawed Mouse Metaphase II Oocytes

Abstract: Background: Oocyte vitrification has been widely used in the treatment of infertility and fertility preservation. However, vitrification-induced mitochondrial damage adversely affects oocyte development. Several studies have reported that mitochondrial calcium uptake protein 1 (MICU1) regulates the uptake of mitochondrial calcium by the mitochondrial calcium uniporter (MCU) and subsequently controls aerobic metabolism and oxidative stress in mitochondria, but research considering oocytes remains unreported. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…In the present study, sheep oocytes showed abnormal elevation of intracellular Ca 2+ levels after vitrification, but intracellular Ca 2+ levels did not change after treatment with PLGA-RES. Although PLGA-RES restored mitochondrial function to a certain extent, a portion of vitrification-induced Ca 2+ could not flow into the medium in time due to ZP hardening caused by vitrification ( Wiesak et al, 2017 ; Lan et al, 2022 ), leading to Ca 2+ overload in the cytoplasm. In general, PLGA-RES had positive effects on the cryopreservation of MII oocytes.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, sheep oocytes showed abnormal elevation of intracellular Ca 2+ levels after vitrification, but intracellular Ca 2+ levels did not change after treatment with PLGA-RES. Although PLGA-RES restored mitochondrial function to a certain extent, a portion of vitrification-induced Ca 2+ could not flow into the medium in time due to ZP hardening caused by vitrification ( Wiesak et al, 2017 ; Lan et al, 2022 ), leading to Ca 2+ overload in the cytoplasm. In general, PLGA-RES had positive effects on the cryopreservation of MII oocytes.…”
Section: Discussionmentioning
confidence: 99%